1983
DOI: 10.1002/mus.880060809
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of different fiber types in human skeletal muscles: Effects of aging studied in whole muscle cross sections

Abstract: The effects of aging on the total number and size of fibers, and the proportion and distribution of type 1 (slow twitch) and type 2 (fast twitch) fibers were studied in cross sections (15 mu thick) of autopsied whole m. vastus lateralis from two age groups. Each group consisted of six, previously physically healthy males (mean age 72 +/- 1 years and 30 +/- 6 years, respectively). The size of the muscles of the older individuals was 18% smaller (P less than 0.01) and the total number of fibers was 25% lower (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
287
1
11

Year Published

1997
1997
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(306 citation statements)
references
References 17 publications
7
287
1
11
Order By: Relevance
“…Baumgartner et al (1995) suggested that the active cell mass may be replaced to a greater extent in women than in men, but had no explanation for this apparent sex difference. Lexell et al (1983) found 18% smaller muscle size and 25% fewer number of muscle cells at autopsy in elderly men (70 ± 73 y) than in young men (19 ± 37 y), which is close to the 16% lower ASMM and 25% lower BCM noted in this study. Thus sarcopenia in elderly subjects may be due to muscle atrophy due to a gradual and selective loss of cell mass, and a decrease in number and size of muscle ®bres (Lexell et al, 1995).…”
Section: Discussionsupporting
confidence: 87%
“…Baumgartner et al (1995) suggested that the active cell mass may be replaced to a greater extent in women than in men, but had no explanation for this apparent sex difference. Lexell et al (1983) found 18% smaller muscle size and 25% fewer number of muscle cells at autopsy in elderly men (70 ± 73 y) than in young men (19 ± 37 y), which is close to the 16% lower ASMM and 25% lower BCM noted in this study. Thus sarcopenia in elderly subjects may be due to muscle atrophy due to a gradual and selective loss of cell mass, and a decrease in number and size of muscle ®bres (Lexell et al, 1995).…”
Section: Discussionsupporting
confidence: 87%
“…It is clear from several previous studies that there is a preferential loss of type II fibers and reduction in type II fiber CSA with age (31,59). Furthermore, recent data using fiber type-specific immunofluorescent microscopy demonstrate that in addition to a preferential loss of type II fiber CSA there is a type II specific loss of SCs per myofiber in older muscle (37,59).…”
Section: Discussionmentioning
confidence: 94%
“…appendicular mass relative to height 2 that is ≤7.23 kg m −2 in men and ≤5.67 kg m −2 in women) and a gait speed of less than 1 m s −1 (Fielding et al 2011). On a myocellular level, sarcopenia is characterized by a reduction in muscle fibre number as well as fibre size, with specific type II muscle fibre atrophy (Lexell et al 1983(Lexell et al , 1988. Muscle mass usually reaches its peak at the age of 25-30 years and thereafter begins to decline (Lexell et al 1988;Janssen et al 2000).…”
Section: Sarcopenia In the Elderly: A Common Problemmentioning
confidence: 99%